IMPLEMENTASI KEBIJAKAN PEMERINTAH KOTA DALAM PENCEGAHAN DAN PENGENDALIAN CORONA VIRUS DISEASE 2019 DI KOTA SAMARINDA (STUDI KASUS PENERAPAN DISIPLIN PROTOKOL KESEHATAN) - ACHMAD RIDZKI ARIYANDA (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
This study aims to determine the implementation of the policy of the Government of Samarinda City in the prevention and control of COVID-19 in Samarinda City Based on the results of the study, that the Samarinda City Government's policies in preventing and controlling COVID-19 have been implemented properly, which can be seen from the environmental conditions that are very supportive of the Samarinda City government's policies in preventing and controlling COVID-19. Relations between organizations have been well established and synergize in communication and coordination between related organizations. Authority, staff, infrastructure, and information are elements of well-implemented resources. Clarity and consistency in implementing policies is carried out with the existence of health protocol patrols. The officers have extraordinary commitment in carrying out the implementation of policies based on the instructions of the Mayor of Samarinda. Keyword : Policy Implementation, COVID-19